The Short Arm of Chromosome Pair 15 Deletion (15p-) of Albino Stump-tailed Macaque (Macaca arctoides) in Laos PDR - Maneechot, Nuntiya; Kaewsri, Sarawut; Patawang, Isara; Jumrusthanasan, Sarun; Pinthong, Krit; Tanomtong, Alongklod (KKU Science Journal, 2015)
The first cytogenetic study of one male and one female of albino stump-tailed macaque, Macaca arctoides (Primates, Cercopithecidae) in, Laos PDR was carried out. Blood samples were collected from this species maintained in Laos Zoo. The standard whole blood lymphocytes were cultured in the presence of colchicine, metaphase cells were spread on slides and air-dried. Conventional staining was applied to stain the chromosome. The results showed that the number of diploid chromosomes of albino stump-tailed macaque was 2n=42, the fundamental number (NF) were 82 in both sexes. The types of autosomes were 18 metacentric, 20 submetacentric and 2 telocentric chromosomes. The X and Y chromosome was the submetacentric chromosome and founded that a chromosome pair 13 is a clearly observable satellite chromosome that has secondary constriction on short arm chromosomes. However, detected abnormality of chromosome pairs 15 is deletion in the short arms (del,XX,XY,42,15p-), cause the transition of chromosome type from submetacentric to telocentric. This might involved in the loss of melanin pigment that causes fractures in albino stump-tailed macaque. The karyotype formula for the albino M. arctoides is as follows: 2n (diploid) 42 = Lm6+Lsm8+Mm4+Msm10+Mt2+Sm8+Ssm2+sex chromosomes (XX/XY)